De-escalation of the Agitated Pediatric Patient: A Standardized Patient Case for Pediatric Residents - Adam Kronish; Daniel Alanko; Victoria R. Quinn; Charles Wulff; Elizabeth Stone; Robyn Wing (Association of American Medical Colleges, 2024)
Introduction Over the past 5 years, pediatric mental health emergencies requiring emergency safety evaluations and inpatient boarding of pediatric patients requiring psychiatric admission have increased. Pediatric trainees must learn to effectively and safely de-escalate a patient with agitated or aggressive behavior, as mental health patients take up a larger proportion of their patient population. This standardized patient case addresses gaps in knowledge and skills to ameliorate the care of children and adolescents with behavioral crises in the hospital. Methods Resident learners were presented with a teenage patient admitted to the hospital and awaiting inpatient psychiatric placement for suicidal ideation who became acutely agitated with aggressive behaviors. Learners were expected to attempt to verbally de-escalate the patient and select an appropriate pharmacologic agent for decreasing agitation in the patient. A standardized debrief was conducted with the assistance of child and adolescent mental health experts. Results Twenty-two learners participated in this activity. Residents' confidence in their management skills of the acutely agitated pediatric patient significantly increased after completion of the activity. Seventy-three percent of learners felt confident or very confident in their de-escalation skills at the end of the case, and 86% agreed that the case improved their confidence in managing acute agitation scenarios on the inpatient wards. Discussion This case led to overall increased self-efficacy in caring for the acutely agitated pediatric patient. Future iterations may include multidisciplinary learners of various skill levels and evaluating changes in patient-centered outcomes, such as restraint use, after implementation of the case.